INCIDENCE OF TRACHEOSTOMY IN WEANING FROM MECHANICAL VENTILATION (Fiep Bulletin - online, 2012)
Were admitted to the Intensive Care Unit (ICU) of the University Hospital of the West of Paraná, 339 patients, only 213 participated by presenting the sample aged 15 years and more than 24 hours on mechanical ventilation (MV), of these, 140 sex male (65.73%) being the major cause of trauma admission 50 (38.57%), followed by 32 surgical (22.85%) respiratory and 21 (15%) in sex and 73 females (34.27 %) with the major cause of admission from other causes 16 (21.92), followed by 15 surgical (20.54%) respiratory and 14 (19.17%). Overall, the major cause of admission was trauma (30.51%), followed by surgery (22.06%) and respiratory (16.43%). In 87 patients (40.84%) tracheostomy was performed, while the other 69 patients there was no attempt at weaning. The median preoperative mechanical ventilation tracheostomy was 9.5 (± 4.63) and after 10.5 days (± 7.12) days. Failed withdrawal of mechanical ventilation in patients with tracheostomy on average 5 (± 2.89) times. Before performing the tracheostomy 49 patients (56.32%) were sedated. The pre tracheostomy ventilation mode was used: 47 in synchronized intermittent mandatory ventilation - SIMV (54.02%), 25 assisted controlled ventilation - A/C (28.40%), 13 with continuous positive airway pressure - CPAP (14.77%) and 2 with oxygen - Ayre (2.29%). In the 70 tracheostomized patients were high (80.45%). Of the total sample of 147 patients were discharges from the ICU (69.01%). In this work the tracheotomy did not accelerate the weaning process, and it was not indicated due to the long duration of mechanical ventilation was not indicated because it is a difficult and not by weaning obstruction, but held by decision of the attending intensivist.
Keywords: Respiration; Artificial; Tracheostomy; Weaning